Analysis of Body Composition and Physical Fitness Variables of Korean Middle School Students: National Fitness Award (2018-2022) - Dong Hyun Yoon; Kwang-Jun Kim (Asian Society of Kinesiology, 2024)
OBJECTIVES The purpose of this study is to analyze the trend of yearly changes in adolescent body composition and health-related physical fitness variables using National Fitness Award. METHODS We sampled 209.924 adolescents (age: 13.99 ± 0.85) and investigated their body composition, muscle strength, and cardiopulmonary function. Subgroups by year (2018, 2019, 2020, 2021, 2022) were compared using one-way analysis of variance and frequency analysis tests. RESULTS In the subgroup classified by year, there were significant differences between groups in height, BMI, and gender, and there were significant differences between groups in relative grip strength, 20m PACER, and maximal oxygen consumption. CONCLUSIONS In conclusion, this study presents changes in body composition, muscle strength, and cardiopulmonary function by year as basic data to help understand adolescents' health conditions, and it is expected to provide data that can have a positive impact for future use as clinical and public health information.